Drug Use and School Dropout: A Longitudinal Study - Annis, Helen; Watson, Carol (Canadian Journal of Counselling and Psychotherapy, 2012)
A longitudinal design was employed to study the relationship between drug use and school dropout in a general high school population.Nine hundred and fifteen students enrolled in Grade 9 classes were initially questioned concerning their use of drugs (Time 1). Thirteen months later, those students who had dropped out of school as well as those students still attending classes were asked to report again on their current druguse practices (Time 2). The results supported previously reported findings by demonstrating greater use of most licit and illicit drug categories byschool dropouts following their withdrawal from school (Time 2). Furthermore, it was shown that for almost every drug, the trend towards greater drug use within the dropout group was evident and equally strong before the dropping out occurred (Time 1). There was, however, some indication that dropouts were additionally more likely to start or initiate some categories of drug use following school dropout. The findings were discussed in terms of a "symptom" versus "cause" view of school dropout in relatio to drug use. It was concluded that drug use functions as part of the constellation of contributing factors that precedes dropping out of school, but that dropout status itself may play a causal role in fostering self-identification and/or social group contacts which promote the development of drug abuse patterns.